Міжнародний захист виборчих прав громадян - Мозоль, С.А. (Правова держава: Щорічник наукових праць, 2010)
Стаття присвячена питанням міжнародного захисту виборчих прав громадян України. Розглянуто процедуру захисту виборчих прав громадян України у міжнародних інстанціях. Визначено особливості розгляду скарг про порушення виборчих прав громадян Комітетом ООН з прав людини та Європейським судом. Статья посвящена вопросам международной защиты избирательных прав граждан Украины. Рассмотрена процедура защиты избирательных прав граждан Украины в международных инстанциях. Определены особенности рассмотрения жалоб о нарушении избирательных прав граждан Комитетом ООН по правам человека и Европейским судом. The article deals with the issues of international protection of electioral rights of the citizens of Ukraine. The procedure of protection of electioral rights of Ukrainian citizens in the international institutions is described. The peculiarities of complaints review as to violation of electoral rights protection of Ukrainian citizens by UN Commission on Human Rights and by the European Court are defined.